PERUBAHAN TUTUPAN LAHAN TERHADAP PENURUNAN POPULASI JALAK BALI DI KEPULAUAN NUSA PENIDA - Fadlan Pramatana; Jarwadi B Hernowo; Lilik B Prasetyo (Wana Lestari, 2020)
The population of bali starling shows decrease fluctuations and one of program for conservation through release outside their natural habitat on Nusa Penida. Bali starling’s release activity has been carried out in Nusa Penida islands and the birds can be survive to breed. In 2010, the success program had decreased and the land cover changes could be one of the cause of the population decrease in their natural habitat. This study was aimed to analyze the decline population of bali starling in Nusa Penida islands based on land cover change. Land cover datas were obtained by unsupervised classification and supervised classification method with land cover validation point. The result of the land cover analysis in 2005, 2009, 2010, and 2016 consist of mangrove, shrubs, mix plantation or mix garden, open land, and settlements. In 2009, the land cover was dominated by mix plantation (38.88%) and shrubs (28.88%), while in 2010 it was dominated by mix plantation (26.84%) and shrubs (24.11%). Land cover changes in Nusa Penida islands as the introduction area for bali starling do not show the significant differences. The variabel of decreasing land quality in that location cannot be a factor causing the decline bali starling population.